Notes from the field: Failing to thrive? (Medicine Anthropology Theory, 2020)
Every day in my work as a resident physician, I deny my patients’ particular wishes about living and dying. It is not that I desire to be inhumane; rather, on a daily basis in my job, I am tasked with caring for patients who have been clinically marked with the diagnosis ‘failure to thrive’, in some way deeming them as unsafe to live out in the world. In this think piece, I trace the evolution of this term and what its growing use might mean. As a medical anthropologist, I feel deeply conflicted about these situations that physicians encounter routinely. And as I probed this internal conflict, I realized that the clinical diagnosis of ‘failure to thrive’ is actually an attempt by physicians to grapple with how the social world becomes embodied within our aging or chronically ill populations. Caring for these patients is a complicated, consuming task that also must be further illuminated in relation to the failures of self-care among trainees and practitioners of medicine. I consider here how anthropological theories of care and well-being of both patients and providers can illuminate this ongoing phenomenon of ‘failure to thrive’ among patients who are increasingly at the social margins.